La dinámica familiar y el bajo rendimiento académico de estudiantes con conductas disruptivas de Octavo Año de Educación General Básica - Flores Cárdenas, Martha Verónica (2020)
The purpose of this research is the form that affects family dynamics in students with low academic performance who present disruptive behaviors of Eighth year of basic general education, in the Emilio Estrada Carmona fiscal educational unit, 2018-2019 school period. In which disruptive behavior problems were detected in students such as: contempt of authority, they do not follow the guidelines that indicate them, little interest in the different subjects and as a result they have low academic performance. The methodology that was applied allowed to obtain direct information, with a mixed approach, supported by a descriptive correlational, field and bibliographic research and the theoretical framework with the various theoretical references…….